Landsat-7/ETM + and SRTM images as auxiliary tools to identify lateritic profiles-example in bom jesus da Penha (MG). - Faria Júnior, Ilio Rodarte [UNESP]; Luvizotto, George Luiz [UNESP]; Rosolen, Vania [UNESP] (My University, 2018)
The Brazilian territory has large areas covered by lateritic profiles and their studies have diverse motives. These profiles shows an internal structure with horizons that vary, vertically, in their chemical and mineralogical compositions, and the development of the lateritic processes is inseparable from the characteristics of the model. Then, the exposures of the horizons of a weathering event are associated to features and positions of the relief. Using chemical-mineralogical variations and position on the relief, it is possible apply remote sensing techniques to delimitate answers from those outcrops horizons. Here, the characterization of a lateritic profile neighbor to Bom Jesus da Penha town (MG), developed from gneisses, chlorite-amphibole schists and quartzites, was made by mineralogical characterizations (X-ray diffraction) of samples from different horizons of the metaultramafic schist domain. In sequence, were applied spectral compositions of Landsat-7/ETM+ satellite images and digital elevations and declivity models of the relief, generated by SRTM 1Arc-sec radar images. Thus, the objective was to identify spectral answers to distinct weathering horizons described in the fieldwork. This remote sensing treatment allowed to delimit areas with characteristics related to the superior horizons of the lateritic profile identified in the fieldwork.
Imagens landsat-7/ETM+ E SRTM como ferramentas auxiliares na identificação de perfis lateríticos – Exemplo em bom jesus da Penha (MG).
Keywords: Greenstone belt Morro do Ferro; Metaultramafic rock; Remote sensing; Weathering profile